ANOMALY, Jonathan. Creating Future People: The Ethics of Genetic Enhancement, Routledge, 2020, 109 pp., ISBN 9780367203122. - Dávila Morán, Roberto Carlos (Revista de Filosofía, 2021)
Reseñas de libros actuales.